93.9k views
5 votes
Question provided in picture, answer in the picture is incorrect

Question provided in picture, answer in the picture is incorrect-example-1
User DShah
by
4.8k points

1 Answer

7 votes

Given the system of equations:


\begin{gathered} x+y=6\text{ (eq. 1)} \\ y=-3x\text{ (eq. 2)} \end{gathered}

Substituting equation 2 into equation 1 and solving for x:


\begin{gathered} x+(-3x)=6 \\ -2x=6 \\ (-2x)/(-2)=(6)/(-2) \\ x=-3 \end{gathered}

Substituting x = -3 into equation 2:


\begin{gathered} y=-3(-3) \\ y=9 \end{gathered}

The solution is (-3, 9)

User Deepanmurugan
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.